Effects of dietary nisin supplementation on the growth performance, serum biochemistry, digestive enzyme activities, intestinal morphology, and intestinal microbiota in rabbits - Wu, Xinyu; Shao, Tiancheng; Huang, Yee; Cui, Xuemei; Luo, Yanfang; Ji, Quanan; Hu, Zizhe; Teng, Sheng; Bao, Guolian; Liu, Yan (Frontiers in Veterinary Science, 2025)
IntroductionThis study evaluated the impact of dietary supplementation with varying doses of nisin (NI) on the growth performance, serum biochemical parameters, intestinal digestive enzyme activity, short-chain fatty acid (SCFA) profiles, mucosal morphology, and the cecal microbiota composition in rabbits.MethodsHealthy female New Zealand white rabbits (5 weeks old; n = 90) of comparable body weight were randomly allocated to five groups: a positive control (PC) group receiving a basal diet supplemented with kitasamycin (300 mg/kg), three NI groups supplemented with nisin at 600 (NI600), 800 (NI800), or 1,000 (NI1000) mg/kg, and a negative control (NC) group receiving the basal diet without additives. Each treatment was comprised of three replicates (n = 6 per replicate), and the trial lasted 42 days.ResultsThe results showed that the rabbits administered NI displayed significantly enhanced final body weights as compared to the NC group (P < 0.05), with a dose-dependent effect. Notably, the NI800 and NI1000 groups exhibited a superior average daily gain (ADG) and average daily feed intake (ADFI). Serum analyses showed improved lipid profiles and elevated antioxidant enzyme activities concomitant with reduced lipid peroxidation in the NI-supplemented groups. Enzymatic assays indicated elevated duodenal a-amylase activity in the NI800 group as compared to the PC (P < 0.05) and enhanced ileal trypsin activity in the NI800 as compared to NI1000 and PC (P < 0.05). Histological evaluation confirmed that the NI800 group displayed optimal intestinal villi morphology, characterized by increased density, height, and structural integrity relative to the PC and NC controls. Metagenomic analysis of the cecal microbiota further revealed dose-dependent shifts in the diversity and composition of the microbiota, with the NI800 group exhibiting pronounced restructuring. Enriched functional pathways in the NI groups, including cofactor/vitamin metabolism, amino acid biosynthesis, energy homeostasis, and environmental adaptation.DiscussionCollectively, these findings highlight that NI supplementation enhances digestive efficiency, augments systemic antioxidant defenses, fortifies intestinal barrier function, and modulates microbial ecology and SCFA production, there by promoting growth and metabolic health in rabbits. Nisin, especially at 800 mg/kg, demonstrates significant potential as an antibiotic alternative.